2020
DOI: 10.1002/pen.25478
|View full text |Cite
|
Sign up to set email alerts
|

Comparative computational analysis of dispersive mixing in extension‐dominated mixers for single‐screw extruders

Abstract: Enhanced dispersive mixing can be achieved by harnessing extensiondominated flows, because they are more efficient in agglomerate/droplet breakup than shear-dominated flows. Herein, we compare computationally the performance of two single-screw extrusion mixing sections with significant extensional flow components, the Chris Rauwendaal dispersive (CRD) mixer and the extensional mixing element (EME), recently proposed by the authors. Tapered slots in the CRD and hyperbolic contractions in the EME attempt to cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, for certain materials, such as shear-sensitive ones, shear flow fields can induce excessive shear viscosity heating [7] and damage fibrous components [8], significantly compromising material properties. Research indicates that, under similar stretching or shearing rates, extension-dominated flow mixing exerts twice the maximum force on solid particles compared to shear flow mixing [9][10][11]. Consequently, extension-dominated flow mixing offers higher dispersion efficiency and more effective dispersion effects, albeit with greater difficulty in acquisition and control compared to shear flow fields.…”
Section: Introductionmentioning
confidence: 99%
“…However, for certain materials, such as shear-sensitive ones, shear flow fields can induce excessive shear viscosity heating [7] and damage fibrous components [8], significantly compromising material properties. Research indicates that, under similar stretching or shearing rates, extension-dominated flow mixing exerts twice the maximum force on solid particles compared to shear flow mixing [9][10][11]. Consequently, extension-dominated flow mixing offers higher dispersion efficiency and more effective dispersion effects, albeit with greater difficulty in acquisition and control compared to shear flow fields.…”
Section: Introductionmentioning
confidence: 99%
“…One of the pioneers within the field of mixing is Ica Manas-Zlaczower [6][7][8][9][10][11]. Her famous dispersive mixing index from 1992 is still used today [12][13][14][15][16][17], along with her distributive Cluster Distribute Index [12,17,18]. There have not been many alternatives to Zlaczower's dispersive mixing index.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment results together with the simulation of PS/PMMA blending process proved that the new device was more efficient in dispersing and mixing. Pandey and Maia [21][22][23] introduced hyperbolic flow channels into the mixing elements of extruders to generate extensional flow, and results showed that the extruders with elongational mixing elements were the better dispersive mixer competed with normal extruder mixers.…”
Section: Introductionmentioning
confidence: 99%